ACCEPTANCE OF ARTIFICIAL INTELLIGENCE INFLUENCER IN CONSUMER PURCHASE INTENTION - Rathnakaran, Arun Prasad (Digital Repository of Theses - SSBM Geneva, 2023)
Influence is something that is as old as humans. We are always under the influence of something or someone. In the same lines, the concept of influencer marketing has been on the rise among the consumers in the recent past. Marketing has seen a new phase of growth with influencers posting content in social media. These influencers are followed by thousands to a million followers and even more at times. These make the brands consider these influencers to be potential advocates of their brands. Today, with the rise of Artificial Intelligence across the globe, the combination of Artificial Intelligence and Influencer Marketing has led to “Artificial Intelligence Influencer” creating disruptions in the industry. AI Influencers are the order of the day for marketers with the rapid growth of technology. This has come as a game changer in the influencer industry. AI Influencers prove to be more effective than the human counterparts. They have been able to generate content, provide personalized posts to consumers, create positive experiences and customer engagement across various social media platforms. The AI Influencers have been on the limelight since their introduction. The play a very critical role in bringing the brands and consumers together. This gives us the required space and motivation to study how these AI Influencers are being perceived by the consumers. It also explores the impact of these AI influencers towards customers’ purchase intention. On reviewing related literatures, it is understood that there is scope for research in the AI Influencer space. This research attempts to empirically identify the factors that persuade Indian consumers towards AI Influencers in their purchase intention. It uses judgmental sampling and descriptive research in the study. The complete model was validated using Structural Equation Model. This research exhibits the theoretical and managerial implications and acceptance of AI Influencers towards customer purchase intentions. The study reveals there are no differences in how personalization is seen indicating that both human & AI influencers are equally capable of tailoring content.